Strain-Specific Restriction of the Antiphagocytic Property of Group A Streptococcal M Proteins - Kotarsky, Heike (American Society for Microbiology, 2000)
Group A streptococcal M proteins are type-specific virulence factors that inhibit phagocytosis. We used two M proteins, M5 and Emm22, to analyze the influence of genetic background on the properties of M proteins. Mutant strains, engineered to lack these M proteins, were complemented with genes encoding the homologous or heterologous M protein, and the complemented strains were analyzed for phagocytosis resistance. Neither the M5 nor the Emm22 protein conferred phagocytosis resistance in the heterologous background, but they did do so in the homologous background. This was not due to lack of surface expression in the heterologous background. Moreover, the M5 and Emm22 proteins expressed in heterologous background appeared to have normal structure, since they were not affected in their ability to bind different human plasma proteins. In particular, M5 or Emm22 had normal ability to bind human complement inhibitors, a property that has been implicated in phagocytosis resistance. Results similar to those obtained with M5 and Emm22 were obtained in experiments with the M6 and Emm4 proteins. Together, these data suggest that the surface expression of M protein alone may not be sufficient to confer phagocytosis resistance and consequently that strain-specific factors other than M and Emm proteins may contribute to the ability of group A streptococci to resist phagocytosis.